Hubungan Public Speaking dan Personal Branding MC terhadap Kepuasan Audiens Choky Sitohang - Jaya, Suhendra Saputra; Subagio, Aris (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the relationship between public speaking skills and personal branding of a Master of Ceremony (MC) on audience satisfaction using a quantitative approach. The research was conducted to understand how the abilities and image of an MC contribute to shaping positive audience perceptions. The instruments used in this study were tested for validity and reliability, and the results confirmed that they were valid and reliable. However, based on the Shapiro-Wilk test, the data were found to be non-normally distributed, so further analysis used non-parametric techniques. The findings indicate that both public speaking skills (r = 0.699; p = 0.000) and personal branding (r = 0.720; p = 0.000) individually have a strong and significant relationship with audience satisfaction. When analyzed simultaneously, both variables significantly affect audience satisfaction (F = 46.653; p = 0.000) and explain 71% of the variance in audience satisfaction (R Square = 0.710). These results highlight that effective communication, confidence, and a well-developed personal image are essential factors for MC in delivering meaningful, professional, and enjoyable experiences for their audiences.